UV-B Induces Distinct Transcriptional Re-programing in UVR8-Signal Transduction, Flavonoid, and Terpenoids Pathways in Camellia sinensis - Shamala, Lubobi Ferdinand; Zhou, Han-Chen; Han, Zhuo-Xiao; Wei, Shu (Frontiers in Plant Science, 2020)
Plants are known to respond to Ultraviolet-B radiation (UV-B: 280-320 nm) by generating phenolic metabolites which absorbs UV-B light. Phenolics are extraordinarily abundant in Camellia sinensis leaves and are considered, together with pleasant volatile terpenoids, as primary flavor determinants in tea beverages. In this study, we focused on the effects of UV-B exposure (at 35 μW cm-2 for 0, 0.5, 2, and 8 hr) on tea transcriptional and metabolic alterations, specifically related to tea flavor metabolite production. Out of 34,737 unigenes, a total of 18,081 differentially expressed genes (DEGs) due to UV-B treatments were identified. Additionally, the phenylpropanoid pathway was found as one of the most significantly UV-B affected top 20 KEGG pathways while flavonoid and monoterpenoid pathway-related genes were enhanced at 0.5 hr. In the UVR8-signal transduction pathway, UVR8 was suppressed at both short and long exposure of UV-B with genes downstream differentially expressed. Divergent expression of MYB4 at different treatments could have differentially altered structural and regulatory genes upstream of flavonoid biosynthesis pathways. Suppression of MYB4-1&3 at 0.5 hr could have led to the up-regulation of structural CCOAOMT-1&2, HST-1&2, DFR-4, ANR-2, and LAR-1&3 genes resulting in accumulation of specialized metabolites at a shorter duration of UV-B exposure. Specialized metabolite profiling revealed the correlated alterations in the abundances of catechins and some volatile terpenoids in all the treatments with significant accumulation of specialized metabolites at 0.5 hr treatment. A significant increase in specialized metabolites at 0.5 hr treatment and no significant alteration observed at longer UVB treatment suggested that shorter exposure to UV-B led to different display in gene expression and accumulation of specialized metabolites in tea shoots in response to UV-B stress. Taken together, our results indicated that the UV-B treatment applied in this study differentially altered the UVR8-signal transduction, flavonoid and terpenoid pathways at transcriptional and metabolic levels in tea plants. Our results show strong potential for UV-B application in flavor improvement in tea at the industrial level.